Toremifene Decreases Vertebral Fractures in Men Younger Than 80 Years Receiving Androgen Deprivation Therapy for Prostate Cancer - Smith, Matthew R. (2011)
PURPOSE: Androgen deprivation therapy (ADT) is associated with increased fracture risk. In a recent Phase III trial, toremifene significantly decreased vertebral fractures in men receiving ADT. Similar to other selective estrogen receptor modulators, toremifene was associated with an increase in venous thromboembolic events (VTEs), with the greatest risk in men aged ≥80 years. This post hoc analysis evaluated the efficacy and safety of toremifene in men aged <80 years. MATERIALS AND METHODS: This analysis included 847 subjects aged <80 years; 430 received toremifene 80 mg by mouth daily and 417 received placebo for up to 24 months. The primary endpoint was new vertebral fractures. Secondary endpoints included fragility fractures, bone mineral density (BMD), and safety. RESULTS: Compared with placebo, toremifene decreased the relative risk of new vertebral fractures by 79.5% (95% CI, 29.8%–94.0%; P<0.005). New vertebral fracture incidence was 1.0% with toremifene and 4.8% with placebo (absolute risk reduction, 3.8%). Compared with placebo, toremifene significantly reduced the incidence of a nontraumatic fracture or >7% bone loss by 24 months (P<0.0001). Toremifene also significantly increased BMD at all measured sites (P<0.001 for all comparisons). The incidence of VTEs was similar in the toremifene and placebo groups (2.1% vs 1.0%, respectively; P=0.26). Rates of other adverse events were also similar between groups. CONCLUSIONS: Toremifene significantly decreased new vertebral fractures in men aged <80 years receiving ADT for prostate cancer. The risk of VTEs was lower than in the overall study population, suggesting an improved benefit–risk profile in younger men.